1997
DOI: 10.1109/77.620744
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear response of HTSC thin film microwave resonators in an applied DC magnetic field

Abstract: The non-linear microwave surface impedance, Zs = Rs + iXs, of patterned YBCO thin films, was measured using a suspended line resonator in the presence of a perpendicular DC magnetic field, HDC, of magnitude comparable to that of the microwave field, H rf . Signature of the virgin state was found to be absent even for relatively low microwave power levels. The microwave loss was initially found to decrease for small applied HDC before increasing again. Also, non-linearities inherent in the sample were found to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…surface resistance R s and (or) surface reactance X s change non-monotonically with applied mw or dc magnetic field, were observed [16][17][18][19]. Choudhury et al reported an anomalous field dependence of surface resistance R s of a YBCO suspended line resonator in the presence of a weak, perpendicular dc magnetic field at 10K.…”
Section: Introductionmentioning
confidence: 99%
“…surface resistance R s and (or) surface reactance X s change non-monotonically with applied mw or dc magnetic field, were observed [16][17][18][19]. Choudhury et al reported an anomalous field dependence of surface resistance R s of a YBCO suspended line resonator in the presence of a weak, perpendicular dc magnetic field at 10K.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of nonlinearities are not well understood at present, and several groups have reported unexpected features like the recovery of superconductivity [4][5][6][7][8] or non-cubic power dependences of the thirdorder two-tone intermodulation product (IMD) or harmonic generation [9,10].…”
mentioning
confidence: 99%
“…20 It is worth noting that the magnetic recovery effect, connected with a decrease in the microwave absorption for a small dc magnetic field, has been already observed. 35 FIG. 3.…”
Section: Resultsmentioning
confidence: 96%